High fat diet rapidly suppresses B lymphopoiesis by disrupting the supportive capacity of the bone marrow niche. - Benjamin J Adler; Danielle E Green; Gabriel M Pagnotti; M Ete Chan; Clinton T Rubin (PLoS ONE)
The bone marrow (BM) niche is the primary site of hematopoiesis, and cues from this microenvironment are critical to maintain hematopoiesis. Obesity increases lifetime susceptibility to a host of chronic diseases, and has been linked to defective leukogenesis. The pressures obesity exerts on hematopoietic tissues led us to study the effects of a high fat diet (HFD: 60% Kcal from fat) on B cell development in BM. Seven week old male C57Bl/6J mice were fed either a high fat (HFD) or regular chow (RD) diet for periods of 2 days, 1 week and 6 weeks. B-cell populations (B220+) were not altered after 2 d of HFD, within 1 w B-cell proportions were reduced by -10%, and by 6 w by -25% as compared to RD (p<0.05). BM RNA was extracted to track the expression of B-cell development markers Il-7, Ebf-1 and Pax-5. At 2 d, the expression of Il-7 and Ebf-1 were reduced by -20% (p = 0.08) and -11% (p = 0.06) whereas Pax-5 was not significantly impacted. At one week, however, the expressions of Il-7, Ebf-1, and Pax-5 in HFD mice fell by -19%, -20% and -16%, and by six weeks were further reduced to -23%, -29% and -34% as compared to RD (p<0.05 for all), a suppression paralleled by a +363% increase in adipose encroachment within the marrow space (p<0.01). Il-7 is a critical factor in the early B-cell lineage which is secreted by supportive cells in the BM niche, and is necessary for B-cell commitment. These data indicate that BM Il-7 expression, and by extension B-cell differentiation, are rapidly impaired by HFD. The trend towards suppressed expression of Il-7 following only 2 d of HFD demonstrates how susceptible the BM niche, and the cells which rely on it, are to diet, which ultimately could contribute to disease susceptibility in metabolic disorders such as obesity.